In situ beamline analysis and correction of active optics. Erratum. (1st September 2017) - Sutter, John; Alcock, Simon; Sawhney, Kawal
Abstract : A correction to one of the equations in the paper bySutter et al. (2012). [ J. Synchrotron Rad. 19, 960–968] is made. Abstract : A correction to one of the equations in the paper bySutter et al. (2012). [ J. Synchrotron Rad. 19, 960–968] is made.